(untitled) (Research, Society and Development, 2024)
The present study aimed to analyze the relationships between Mandibulofacial Dysostosis and its impact on the oral cavity through an integrative literature review. For this, a search was conducted in the MEDLINE®, IBECS®, LILACS®, and SciELO® databases, using Health Sciences Descriptors (DeCS) related to Mandibulofacial Dysostosis, genetics, Congenital Disorders, and Syndrome, combined with boolean operators AND and OR. The integrative review contributes to evidence-based practice in the health field. Data collection followed six methodological steps: defining the topic, establishing inclusion/exclusion criteria, collecting information from selected studies, evaluating the methods used, interpreting and discussing the results, and presenting the conclusions. The results indicated a scarcity of articles investigating the relationship between congenital factors and impacts on the oral cavity, highlighting the need for more research to establish correlations in this regard.